Analysis of Junior High School Students' Mathematical Problem-Solving Skills in Solving Social Arithmetic Problems - Mardiansyah, Dian; Hendriana, Heris; Supriatna, Tatang; Putra, Harry Dwi ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2025)
Education is the main foundation in character building and individual intellectual abilities. Mathematical problem solving ability is one of the important skills that must be mastered by students in the modern educational era, especially in the context of social arithmetic material that is often applied in everyday life. This study aims to analyze the mathematical problem solving ability of students in class VII-A at SMPN 3 Cisarua in solving social arithmetic problems. This research uses a descriptive qualitative approach with data collection methods through interviews with math teachers and observations of students during the learning process and problem solving. The data analysis process was carried out descriptively to describe the variations in students' problem solving abilities and the factors that influence these abilities. The results of the analysis show that the mathematical problem solving ability of students in class VII-A at SMPN 3 Cisarua still varies, with some students showing significant improvement after the application of the Problem-Based Learning (PBL) learning method. Factors such as student engagement in learning, understanding of mathematical concepts, and critical thinking ability affect students' mathematical problem solving ability. The application of PBL method can be one of the effective strategies to improve student engagement, understanding of mathematical concepts, and mathematical problem solving skills. In conclusion, PBL method is proven to be an effective strategy to improve students' engagement, understanding of concepts, and their mathematical problem solving skills, so it can be implemented more widely in mathematics learning.